Identification of Sensory Attributes That Drive Consumer Liking of Commercial Orange Juice Products in Korea. Issue 9 (2nd August 2013) - Kim, Mina K.; Lee, Young‐Jin; Kwak, Han Sub; Kang, Myung‐woo
Abstract: Orange juice is a well‐accepted fruit juice, and its consumption increases steadily. Many studies have been conducted to understand the sensory characteristics of orange juice throughout its varying processing steps. Sensory language and consumer likings of food can be influenced by culture. The objective of this study is to evaluate the sensory characteristics of commercially available orange juices in Korea and identify drivers of liking for orange juices in Korea. A quantitative descriptive analysis was conducted using a trained panel ( n = 10) to evaluate 7 orange juice samples in triplicates, followed by consumer acceptance tests ( n = 103). Univariate and multivariate statistical analyses were conducted for data analysis. The sensory characteristics of commercially available orange juice were documented and grouped: group 1 samples were characterized by high in natural citrus flavors such as orange peel, orange flesh, citrus fruit, and grape fruit, whereas group 2 samples were characterized by processed orange‐like flavors such as over‐ripe, cooked‐orange, and yogurt. Regardless of orange flavor types, a high intensity of orange flavor in orange juice was identified as a driver of liking for orange juices in Korea. Three distinct clusters were segmented by varying sensory attributes that were evaluated by likes and dislikes. Overall, many similarities were noticed between Korean market segment and global orange juice market. By knowing the drivers of liking and understanding the distinct consumer clusters present in the Korean orange juice market, the orange juice industry could improve the strategic marketing of its products in Korea.